Bose-Einstein condensation in atomic gases - Tokarchuk, M.V. (Condensed Matter Physics, 2002)
The book edited by M.Inguscio, S.Stringari and
C.E.Wieman contains the proceedings of the International
School of Physics “Enrico Fermi” (Course CXL)
which took place at Varenna on Lake Como, 7–17 July
1998. The problem of discussion – phenomenon of
Bose-Einstein Condensation (BEC) in atomic gases
– incorporated both the experiments related to BEC
and theoretical considerations.